ANALYSIS OF UNDERGRADUATE STUDENTS' CREATIVE MATHEMATICAL THINKING ABILITIES - Siti Salamah Br Ginting; Dian Armanto; Izwita Dewi (Universitas Lambung Mangkurat, 2024)
This research aimed to analyze undergraduate students’ mathematical creative thinking abilities (MCTA). This study employs a qualitative descriptive method, with the research subjects being Mathematics Education Study Program students. Tests and interviews were the instruments used for mathematical creative thinking ability. The results of the research show that students' mathematical creative thinking abilities vary, as many as 20% are in the low category (CCTA < 33%), 60% are in the medium category (CCTA between 33% and 67%) and 20% are in the high category (CCTA > 67 %). Understanding mathematical concepts, learning experiences, and motivation all have an impact on students creative mathematical thinking skills. It is hoped that the results of this research can be considered when designing learning that can develop students' mathematical creative thinking abilities. Keywords: analyze, mathematical creative thinking abilities, undergraduate students’